(3SjQI QShd Gddg Udi Gddg Ydjg hSdes - (3YHO Gdedc Hf gTGe Hf CjhH GdMejQj GdeYGaQj, CHh eMeO, LeGd GdOjf,J (B213 (3g` s
(3ChdgG (B:s
(3MOKfG CHh eMeO YHO Gdedc Hf gTGe , bGd (B: (3MOKfG RjGO Hf YHO Gddg GdHcGFi Yf eMeO GHf ESMGb ai GdeWdHi bGd (B: (3ZRG CHh SajGf Hf MQH ZRhI GdShjb ai Pi GdMLi s
(3BNQgG (B:s
(3jG CaVd GdfGS Efi cfJ ai fgQ CUHMJ efg ceKd GdeaQO GdUPi bGd GHf gTGe (B: (3YLR GdHjJ Yf ZjQ GHJ ESMGb s
(3fSNI YGTQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B166 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B192s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B135 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B206 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B238 s
Keywords: (3GdJGQjNs